Prevention of Oxidative Stress and Inflammation by Ashitaba (Angelica keiskei)’s Ethanol Extract - Khafid, Muhamad; Krisnawati, Dyah Ika; Wardani, Erika Martining; Rahayu, Dwi; Setiyowati, Eppy; Rusdianingseh (Trends in Immunotherapy, 2025)
Cigarette smoke (CS) contains a complex combination of thousands of different chemicals that increase oxidative stress. Inhaling CS causes an inflammatory response, which leads to several diseases linked to tobacco. Ashitaba has various derivatives that serve as intermediates in the biosynthesis of one type of bioactive flavonoid antioxidant, which is thought to neutralize oxidative stress events. Ashitaba has also been shown to inhibit platelet aggregation, exhibit vasorelaxant effects, and suppress the differentiation of preadipocytes. Safety studies indicate that administering ashitaba chalcone orally to male Wistar rats for 28 days showed no signs of toxicity. Similarly, gavage administration of ashitaba extract in male ICR mice demonstrated safe absorption and metabolism of 4-hydroxyderricin and xanthoangelol without adverse effects. Additionally, a related compound, xanthohumol, a prenylated chalcone found in hops, was given to female BALB/c mice at approximately 1000 mg/kg daily for three weeks without toxic effects. This study proves that Ashitaba contains antioxidants that can help prevent oxidative stress and inflammation induced by CS. Flavonoids isolated from ashitaba were found to have a flavonoid content of 38.115 ± 0.124 ppm, which was then implemented in in-vivo studies The ability of these antioxidants to decrease the level of pro-inflammatory cytokines in rat blood serum and lung tissue after exposure to CS was investigated. In this study, we isolated flavonoids from ashitaba and obtained a flavonoid, then implemented it for in vivo studies, and the ability of antioxidants in Angelica keiskei to prevent inflammatory events was proved.